Study on the impact of admission systems on higher education outcomes: volume I : comparative report - Haj, Cezar; Usher, Alex; Geanta, Irina; Atherton, Graeme; Orr, Dominic (Publications Office of the European Union, 2017)
The subject of this report is European higher education admission systems. Admission is not a simple process which occurs at the end of secondary education. It is a process which may begin from the moment a student is streamed in secondary schooling and end, in some cases, with post-admission selection at the end of the first year of studies. To get to the core of this process, the study focuses on the impact of schools and higher education institutions (HEIs) in the selection process and on how students themselves end up choosing a pathway and a specific institution and programme of study.